Magic and precious stones in the Old Swedish Eufemiavisa Hertig Fredrik av Normandie - Maria Cristina Lombardi (Filologia Germanica)
This paper focuses on Hertig Fredrik av Normandie – one of the so-called Eufemiavisorna, three anonymous Old Swedish poems (Herr Ivan, Flores och Blanzeflor and Hertig Fredrik av Normandie) – and concentrates on a number of episodes where magic plays a significant role in the development of the narrative, in the aim of analyzing the kind of magic and why it is used in the text as well as to what extent it contributes to shape and spread the new idea of an aristocracy. Translated into Swedish from three continental European romances for Queen Eufemia of Norway at the beginning of the 14th century, Eufemiavisorna were designed to establish a common solid ideological background between Norway and Sweden by transmitting the new continental courtly ideas and norms to the Swedish court. Later, further translated into Old Danish, under the Kalmar Union, they seem to have served the same purpose extended to Denmark, contributing to reinforce the political relationships among the three kingdoms. In particular, their influence on the idea of natural magic expressed in some passages of Hertig Fredrik av Normandie – spread with encyclopedic writings, specifically lapidaries, which had reached Scandinavia between the 11th and 13th century – will be highlighted. I also intend to investigate whether magic could be regarded as an instrument for justifying the royal authority and defending the social order proceeding from it. Finally, correspondences and differences with similar magic-related circumstances, objects and performers occurring in Old Norse texts, will be discussed in order to show how elements of the ancient Scandinavian heritage (familiar to aristocratic audiences) changed, acquiring new aspects, values and meanings aimed at making nobles avoid conflicts and comply with royal demands of political stability.